2017
DOI: 10.1002/ehf2.12205
|View full text |Cite
|
Sign up to set email alerts
|

Clinical practices and attitudes regarding the diagnosis and management of heart failure: findings from the CORE Needs Assessment Survey

Abstract: AimsCORE is a continuing medical education initiative designed to support the evidence‐based management of heart failure (HF) in the primary and secondary care settings. The goal of the CORE Needs Assessment Survey is to describe current clinical practice patterns and attitudes among global stakeholders in HF care.Methods and resultsThe CORE Steering Committee guided the development of survey questions to assess clinical practice, confidence, and attitudes/perceptions among cardiologists, primary care physicia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
1
9
0
2
Order By: Relevance
“…There were no differences in the global scores between specialists and fellows, although fellows performed better for questions on most recent updates, such as the indications for treatment with sacubitril/ valsartan, and specialists on less recent indications, such as loop diuretic indications. Previous surveys reported that the adherence of physicians and nurses to current guidelines on HF was suboptimal [11,12]. This was also true for Geriatrician, as reported by a European survey including nine countries, that showed that a poor knowledge of the relevant guidelines, rather than an objective difficulty in putting them in practice, was at the basis of poor adherence [13].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…There were no differences in the global scores between specialists and fellows, although fellows performed better for questions on most recent updates, such as the indications for treatment with sacubitril/ valsartan, and specialists on less recent indications, such as loop diuretic indications. Previous surveys reported that the adherence of physicians and nurses to current guidelines on HF was suboptimal [11,12]. This was also true for Geriatrician, as reported by a European survey including nine countries, that showed that a poor knowledge of the relevant guidelines, rather than an objective difficulty in putting them in practice, was at the basis of poor adherence [13].…”
Section: Discussionmentioning
confidence: 87%
“…Most of the previously published surveys on the knowledge, clinical attitudes and management of patients affected by HF were mainly addressed to cardiologists and general practitioners or nurses [11][12][13], while geriatricians, who frequently manage patients with this disease, are rarely studied [13]. Furthermore, no survey had included fellows, that are often actively involved in the management of HF in acute care wards.…”
Section: Introductionmentioning
confidence: 99%
“…SOBOTA‐HF study will, with comprehensive transthoracic echocardiography and external independent core echocardiography laboratory centre, be able to investigate the prevalence of three HF phenotypes per LVEF. For the purposes of the primary endpoint, we will apply the ESC guidelines criteria; nonetheless, we will also adopt other criteria for diagnosis of diastolic dysfunction, which will allow the comparison of different approaches, also in conjunction with different natriuretic peptide cut‐offs to suggest the optimal practice to be adopted in daily routine …”
Section: Discussionmentioning
confidence: 99%
“…40 Further, 34% of the patients who had a primary event experienced at least one other HF hospitalization and sacubitril/valsartan had a similar efficacy to reduce recurrent events ( Figure 1). 47,48 Further research is therefore focused on the optimization of medical treatment in HFrEF patients. 42,43 Based on these results, 40,44 sacubitril/valsartan is currently recommended as a replacement for ACEi/ARBs in ambulatory patients with HFrEF who remain symptomatic despite optimal medical treatment.…”
Section: Neurohormonal Antagonistsmentioning
confidence: 99%